Taking equity-mindedness to the next level: the equity-minded organization - Liera, Román; Desir, Steve (Frontiers in Education, 2023)
University and college leaders have an espoused interest in racial equity. In recent years, university and college leaders have invested in diversity, equity, and inclusion (DEI) training that focuses on developing individual attributes that reflect equity-mindedness. For example, DEI training efforts have often been focused on helping faculty develop critical race consciousness by raising their awareness of systemic racism in their routine teaching, mentoring, and hiring practices. However, in many cases, DEI training and equity change efforts primarily focus on individual-level change without critically identifying, disrupting, and transforming organizational processes and policies that perpetuate structural racism. In this paper, we synthesized research on race, organizations, and equity-mindedness to argue that racial equity change efforts should aspire to transform universities and colleges into equity-minded organizations. At the organizational level, equity-mindedness has the potential to structure organizational behavior, shape policy development, and frame practitioner and leader understandings of organizational equity issues in ways that are more aligned with their commitments to equity and justice. Through an analysis of higher education equity change efforts, we introduce a framework for equity-minded organizations. Theorizing equity-mindedness at the organizational level creates opportunities for university leaders, stakeholders, and researchers to move beyond the traditional prose of commitments to DEI to the design of programs, policies, and practices that can lead to more lasting structural changes.